COGNITIVE SEMANTICS ANALYSIS OF ANIMAL PROVERBS IN TOBA LANGUAGE - Elza Leyli Lisnora Saragih; Mulyadi Mulyadi (RETORIKA: Jurnal Bahasa, Sastra, dan Pengajarannya, 2020)
This cognitive semantics study analyzed animal proverbs in Batak Toba language. Descriptive qualitative methods were employed in this study. Preliminary research data were collected from the Umpama and Umapasa Collection of Batak Toba languages written by Richard Sinaga. All proverbs were listened to and grouped by recording and selecting the existing data. In the analysis process, theresearchers conducted interpretation method. In addition, the researcher conducted interviews with three Toba native speakers including the researcher himself, and a Batak-Toba linguist. The results showed that there was 33 lexicon used in Toba Batak proverbs. The animal lexicon consists of mammals (46%), birds (27%), insects (14%), fish (10%), and amphibians (1%). The conceptualization of the animals is both positive and negative. The use of animal in the Toba Batak proverbs not only aims to convey ideas or ideas but can also describe the perceptions, experiences and daily life depictions of the Toba Batak people.